Blended palliative and survivorship care intervention (POISE) for patients with metastatic oncogene-driven non-small cell lung cancer: study protocol for a pilot randomised controlled trial - Jennifer S Temel; Joseph A Greer; Vicki Jackson; Dustin J Rabideau; Heather A Richard; Roshni Sarathy; Jill Feldman; Leslie Cartagena; Heather Patel; Lecia V Sequist; Elyse Park; Laura A Petrillo (BMJ Open)
Introduction Patients with metastatic oncogene-driven non-small cell lung cancer (NSCLC) are experiencing longer and uncertain trajectories of life-limiting illness due to advances in precision medicine. These advanced cancer survivors face new challenges related to living with uncertainty and desire more support to maximize their health and quality of life. Therefore, we developed a population-specific, blended palliative and survivorship care intervention to address the supportive care needs of patients recently diagnosed with advanced lung cancer and who are receiving targeted therapy for NSCLC with EGFR, ALK, ROS1 or RET driver mutations.Methods and analysis This study is a single-site, non-blinded pilot randomised controlled trial of an intervention for patients with metastatic oncogene-driven NSCLC, Patient-centred, Optimal Integration of Survivorship and palliative carE (POISE) versus usual care. POISE consists of a brief series of structured visits with a trained palliative care clinician to address coping with uncertainty, increase prognostic awareness and promote healthy lifestyle behaviours. We will recruit 60 patients from the Massachusetts General Hospital Cancer Center. Patients will be randomised into a 1:1 ratio to the intervention arm or the usual care arm. Patients randomised to the intervention arm will complete four 60 min virtual or in-person visits with a palliative care physician. The usual care arm will receive standard oncology care. Patients in both arms will complete survey assessments at enrolment, 12 weeks and 20 weeks after enrolment, and patients in the intervention group will complete an exit interview. The primary outcome measure of this trial is feasibility, which will be defined by ≥60% enrolment among eligible patients, ≥70% completion of all sessions for participants in the intervention arm and ≥70% completion of all surveys for all study participants. Exploratory outcomes include acceptability, emotional coping with prognosis, self-efficacy for chronic disease management, prognostic awareness, quality of life, anxiety, depression, intolerance of uncertainty and documentation of goals and values discussions in the electronic health record.Ethics and dissemination This study was approved by the Dana-Farber/Harvard Cancer Center’s institutional review board (protocol 20-722). The protocol is reported in accordance with the Standard Protocol Items: Recommendations for Interventional Trials guidelines, and the study will be reported in accordance with the Consolidated Standards of Reporting Trials statement for non-pharmacological trials.Trial registration number NCT04900935.